Clinical profile of hepatocellular carcinoma and experience with sorafenib from a tertiary cancer centre in Southern India - Nandennavar, Manjunath I.; Karpurmath, Shashidhar V.; Mandakalatur, Ganesh; Prasad, Aruna E. (International Journal of Research in Medical Sciences, 2017)
Background: Hepatocellular carcinoma is a major health problem and a major cause of cancer mortality in India. There are no reports published on experience with sorafenib in advanced HCC from India. We analyzed the clinical presentation, possible etiological factors, tumor characteristics, outcomes and tolerability of sorafenib in the patients presenting to present cancer center. Methods: Retrospective chart review of 53 patients was done. 53 patients (male 37, female 16; median age 52 years, range 7-80 years) fulfilling the diagnostic criteria were analyzed for clinical characteristics, hematological and biochemical investigations, tumor characteristics, treatment taken and outcome. Results: 53 patients were diagnosed to have HCC between 2012-2015. Hepatitis B virus infection was the most common underlying etiologic factor (22.6%). Heavy alcohol intake was seen in 5 patients. PS ≥2 was noted in 66% of patients. 68% of the patients had BCLC stage C. Sorafenib was well tolerated with median OS of 3 months in patients taking sorafenib. Conclusions: Most of the patients had advanced inoperable HCC. Majority of the patients presented with BCLC Stage C and D. Hepatitis B infection was the most common underlying etiology. Sorafenib was well tolerated. More prospective studies are required for getting a clearer and correct picture of HCC and experience with sorafenib in Indian scenario.